Dinâmicas, discursos e impactos Da imagem nas exposições de arquitetura - André, Paula (Revelar: Revista de Estudos da Fotografia e Imagem, 2016)
Based on the seminal essay 'From faktura to factography' (1984) by the art historian Benjamin H. D. Buchloh, and referencing the exhibition 'Archivo Universal. La condici6n del documento y la utopia fotografica moderna' (2008), this paper proposes to reveal photograph as documentary instrument, as a discursive resource and as an operating poetic device of urban and architectural culture in the context of the twentieth century. To accomplish its purposes it will be taken as starting point the paradigmatic exhibitions: 'Staatliches Bauhaus Weimar: 1919-1923' (Weimar, 1923); 'Modern Architecture: International exhibition' (New York, 1932, MaMA); 'Architettura rurale italiana' (Milano, 1936, VI Triennale Milano); 'Brazil Builds: Architecture New and Old 1652-1942' (New York, 1943, MaMA); '15 Anos de Obras Publicas 1932-1947' (Lisboa, 1948, IST); 'Architecture without architects: A Short Introduction to Non-Pedigreed Architecture' (New York, 1964, MaMA), seeking to unravel the mechanisms and meanings of urban and architectural body. Beyond the performative and persuasive potential of photogenic cities and architectures laid down in public photos traveled by visitors view's itineraries, one will highlight the expansion of this dynamic vision device, both imagery and documentary through the photographs printed in the catalogs of their exhibitions. Affirming and underlining the role of photography in the formation of an equity awareness and the construction of identity values, we intend to further through a comparative study, show how the picture was questioning and matrix in the construction of urban and architectural culture of the 2oth century. Affirming and underlining the role of photography in the formation of an heritage awareness and in the creation of identity values, one intend to go further through a comparative study to show how photograph was questioning and foundress in the construction of urban and architectural culture of the 2oth century.